2012
DOI: 10.1254/jphs.11082fp
|View full text |Cite
|
Sign up to set email alerts
|

Tea Polyphenols Inhibit Rat Osteoclast Formation and Differentiation

Abstract: Abstract. Matrix metalloproteinases (MMPs) play an important role in degeneration of the matrix associated with bone and cartilage. Regulation of osteoclast activity is essential in the treatment of bone disease, including osteoporosis and rheumatoid arthritis. Polyphenols in green tea, particularly epigallocatechin-3-gallate (EGCG), inhibit MMPs expression and activity. However, the effects of the black tea polyphenol, theaflavin-3,3′-digallate (TFDG), on osteoclast and MMP activity are unknown. Therefore, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 58 publications
4
104
0
1
Order By: Relevance
“…In our findings, a reduction in the clinical scores of joint inflammation and joint erosion were in agreement with the result of trial in which the green tea polyphenol epigallocatechin-3-gallateas a potent antioxidant improves autoimmune arthritis by both regulation of TH17 regulatory cells and inhibition of osteoclasts development [17]. Moreover, there is more evidence that polyphenols in green tea, particularly EGCG, inhibit matrix metalloproteinase activity which plays a fundamental role in pathogenesis of many diseases such as RA [18]. Although, joint erosion in CSS-fed animals reduced, the level of significance in the radiological index of the joints in treated rats compared to control could not be achieved.…”
Section: Discussionsupporting
confidence: 91%
“…In our findings, a reduction in the clinical scores of joint inflammation and joint erosion were in agreement with the result of trial in which the green tea polyphenol epigallocatechin-3-gallateas a potent antioxidant improves autoimmune arthritis by both regulation of TH17 regulatory cells and inhibition of osteoclasts development [17]. Moreover, there is more evidence that polyphenols in green tea, particularly EGCG, inhibit matrix metalloproteinase activity which plays a fundamental role in pathogenesis of many diseases such as RA [18]. Although, joint erosion in CSS-fed animals reduced, the level of significance in the radiological index of the joints in treated rats compared to control could not be achieved.…”
Section: Discussionsupporting
confidence: 91%
“…Epigallocatechin gallate, a bioactive component of green tea, has been reported to inhibit IL-6, a critical proinflammatory cytokine involved in inflammation and bone damage in arthritis (52). Epigallocatechin gallate has also been shown to inhibit the formation and differentiation of osteoclasts via inhibition of MMPs (53). In another study, curcumin (from turmeric) was shown to inhibit overiectomy-induced bone loss by reducing osteoclastogenesis and impaired RANKL signaling (54).…”
Section: Discussionmentioning
confidence: 99%
“…These pilot clinical studies suggest the therapeutic potentiality of SE against oral diseases (114). Tea polyphenols such as epigallocatechin-3-gallate and theaflavin-3,3′-digallate also inhibited the osteoclast formation and differentiation in vitro (115).…”
Section: Clinical Applicationmentioning
confidence: 95%